The adobo road cookbook a Filipino food journey-From food blog. to food truck. and beyond - Gapultos, Marvin (Tuttle Publishing, 2013)
"In The Adobo Road Cookbook, Marvin Gapultos, a food blogger-turned-gourmet food trucker, brings the exotic--yet easy to make--flavors of the Philippines into your home.With a distinct lack of Filipino restaurants to be found, the road to great Filipino food begins and ends at home. In his debut cookbook, Marvin demonstrates that Filipino cuisine can be prepared in any kitchen--from Manila to Los Angeles and everywhere in-between. Marvin interprets traditional Filipino flavors with equal parts kitchen savvy and street smarts--providing easy-to-follow, tried-and-true recipes that serve as a guide to the pleasures of Filipino cooking. The nearly 100 recipes in these pages pave a culinary road trip that transports home cooks to the roadside food stalls, bars and home kitchens of the Philippines, to the hungry streets of L.A., and even into the kitchens of Marvin's grandmother, mother and aunties.A highly personal take on traditional Filipino cooking, The Adobo Road Cookbook boasts a tantalizing mix of native Filipino flavors, as well as influences from Spain, Mexico, China, and the U.S. From chapters featuring surefire entertaining foods like Filipino bar food, street food and cocktails to a complete section of adobo recipes, both traditional and with a twist, the recipes found in The Adobo Road Cookbook express Marvin's unique approach to cooking. All of his recipes emphasize their authentic Filipino roots, taking advantage of traditional island flavors for which the Philippines is rightly renowned.Recipes include: Slow-Braised Pork Belly and Pineapple Adobo Spicy Sizzling Pork (Sisig) Salmon and Miso Sour Soup (Sinigang) Chili Crab Spring Rolls (Lumpia) Coconut Milk Risotto with Kabocha Squash and Long Beans Chicken Adobo Pot Pies Sweet Corn and Coconut Milk Panna Cotta Spicy Sizzling Pork Gin Fizz Tropical Banana-Nut Spring Rolls "-- Provided by publisher.